2001
DOI: 10.1097/00006534-200111000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Traction Avulsion Amputation of the Major Upper Limb: A Proposed New Classification, Guidelines for Acute Management, and Strategies for Secondary Reconstruction

Abstract: Major replantation of a traction avulsion amputation is undertaken with the goal of not only the reestablishment of circulation, but also functional outcome. This type of amputation is characterized by different levels of soft-tissue divisions involving crushing, traction, and avulsion injuries to various structures. Between 1985 and 1998, 27 cases were referred for secondary reconstruction following amputation of the upper extremity involving both arm and forearm. Replantation was performed by at least 12 qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 23 publications
1
36
0
1
Order By: Relevance
“…The published case series are small and there is no scoring system to help with the immediate decisions. The best proposed classification of type of amputation with prognostic significance is that of Chuang and colleagues [3]. Our results support the reliability and importance of this classification.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The published case series are small and there is no scoring system to help with the immediate decisions. The best proposed classification of type of amputation with prognostic significance is that of Chuang and colleagues [3]. Our results support the reliability and importance of this classification.…”
Section: Discussionsupporting
confidence: 80%
“…Our results support the reliability and importance of this classification. We found that classifying the amputation type based on disruption points of muscles and nerves as proposed by Chuang and colleagues [3], rather than the level of detachment of bone created groups of patients with need for similar secondary surgical procedures and final functional result. In the arm level replantation group only type 2 and 3 injuries were encountered, with almost twice as many secondary procedures performed in the type 3 group.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations